PERSEPSI SISWA TERHADAP PEMBELAJARAN MUSIK TRADISIONAL DI SMP NEGERI 27 PADANG - Vulfia Novi Yeska; Ardipal Ardipal; Jagar Lumban Toruan (FBS Universitas Negeri Padang, 2013)
Abstrack Type a descriptive study which describe the students' perceptions of learning the art of traditional music at SMP 27 Padang. The samples used were 44 students. Based on the analysis, it can be concluded: 1) Understanding Student Learning Against Traditional Music in SMP 27 Padang categorized Good that where 38 people (87.11%) respondents stated always (SL) and Frequently (SR), 2) students' reactions to learning traditional music at SMP 27 Good Enough categorized Padang where 35 people (77.96%) respondents stated always (SL) and Frequently (SR), 3) Acceptance of students towards learning the art of traditional music at SMP 27 Padang, where 32 are categorized Good Enough people (73.24%) respondents stated always (SL) and Frequently (SR). Kata kunci: Persepsi, Musik, Tradisional, Deskriptif